Low Birth Weight as Risk Factor of Pneumonia Child in Primary Health Care of Surabaya - Puspamaniar, Vania Ayu; Setyoningrum, Retno Asih; Susanti, Dwi (Universitas Airlangga, 2019)
Introduction: Pneumonia is an infectious disease attacking lower respiratory tract. It has one of the highest number of world's mortality and morbidity in children. Many risk factors are suspected as the reasons why the disease still occur a lot. One of the major risk factors is birth weight which makes their immune system immature and easier to get various complications and infections. The aim of this study is to analyze birth weight as risk factor of pneumonia in children under 5 years old. Methods: This was an analytical study with case control design. This study was held in Primary Health Care of Tambakrejo, from August to December 2017. The sample size was 22 respondents for each case and control group. Technique of sampling was total sampling. Secondary data were collected by medical records at the health center and Kartu Menuju Sehat (KMS). Data were entered into Microsoft Excel then statistically analyzed using IBM SPSS 22. The data were analyzed by Fisher's Exact Test.Results: During August to December 2017, there were 22 respondents which were diagnosed with pneumonia in Tambakrejo Primary Health Center. Two of them (4.55%) had low birth weight and the rests had normal birth weight (95.45%). The analyze result stated that there is no significant correlation between pneumonia incidence and birth weight. Conclusion: Birth weight is one of pneumonia risk factors without significant impact.